2021
DOI: 10.12659/msm.930081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Limitation of Movement of the First Metatarsophalangeal Joint on the Biomechanics of the Ipsilateral Hip, Knee, and Ankle Joints During Walking

Abstract: Background We analyzed the effect of limitation of movement of the first metatarsophalangeal joint (FMJ) on the biomechanics of the lower limbs during walking. Material/Methods Eight healthy college students completed walking under barefoot (BF) and FMJ constraint (FMJC) conditions. We synchronously collected kinematics and dynamics data, and calculated the torque, power, and work of hip, knee, and ankle joints. Results Compared with normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Kinetic evaluation was performed in a gait laboratory, using a three-dimensional gait analysis system (including a 6-camera motion analysis system and a force plate), in a blinded manner by the same assessor [ 18 ]. A 10-meter-long runway served as the patient’s walking route.…”
Section: Methodsmentioning
confidence: 99%
“…Kinetic evaluation was performed in a gait laboratory, using a three-dimensional gait analysis system (including a 6-camera motion analysis system and a force plate), in a blinded manner by the same assessor [ 18 ]. A 10-meter-long runway served as the patient’s walking route.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the unhealthy lifestyles of college students such as indifference to health awareness, long desk time, insufficient physical exercise, insufficient sleep, and irregular work and rest, the physical condition of college students is not optimistic (Mao Zhenming et al, 2022). Xu, R et al (2021) found that after the joint function is limited, the body will compensatory increase the activity level of surrounding muscles to maintain dynamic balance during exercise. Although the physical fitness test of college students is held every year, the content of the test cannot reflect the problems related to the joint function of college students, and the students were not aware of their joint function problems.…”
Section: Literature Review 1 Functional Movement Limitationsmentioning
confidence: 99%
“…We refer to our previous experimental methods [18], Recruit The equipment used in this experiment is mainly composed of the gait walking test bench (Figure 1A), the data acquisition system, and the FMJC device (Figure 1BC). The FMJC device used in the test consists of a low-temperature thermoplastic sheet provided by Convalesce ® , medical gauze and Velcro marking points.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…[11,12]. The flexion and extension of the MJ will have an important The results of our previous research show that [18], the FMJ constraint (FMJC) condition will increase the energy consumption of the ipsilateral ankle, knee, and hip joints. When the FMJ is restricted, the body mainly performs load generation through the ipsilateral hip, knee, and ankle joints.…”
Section: Introductionmentioning
confidence: 99%